Improving Efficiency in the Shelf Manufacturing Process - Thongduang, Thanong; Kanchanapen, Ekkalak; Kaewdee, Chatchai; Sudsomboon, Weerayute; Pansrinual, Weeraphol (Academic Journal of Industrial Technology Innovation, 2023)
The purpose of this research is to suggest the guidelines to improve shelves manufacturing process and analyze the economic value using Value Stream Mapping (VSM), quality tools and cause and effect diagrams to improve such process. The results showed that the assembly was the most time-consuming, followed by packing, cutting and glued laminated timber processes. A development of workpiece holder has been suggested to solve the assembly time. After improving, it was found that the assembly of one piece was reduced from 540minutes to 45 minutes. The analysis of cost benefit analysis found that cost savings of 50 percent and the return of investment was two months and nine days.